2010
DOI: 10.1073/pnas.0910249107
|View full text |Cite
|
Sign up to set email alerts
|

Promoting social behavior with oxytocin in high-functioning autism spectrum disorders

Abstract: Social adaptation requires specific cognitive and emotional competences. Individuals with high-functioning autism or with Asperger syndrome cannot understand or engage in social situations despite preserved intellectual abilities. Recently, it has been suggested that oxytocin, a hormone known to promote mother-infant bonds, may be implicated in the social deficit of autism. We investigated the behavioral effects of oxytocin in 13 subjects with autism. In a simulated ball game where participants interacted with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
598
6
14

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 813 publications
(640 citation statements)
references
References 33 publications
22
598
6
14
Order By: Relevance
“…Interestingly, the AVPR1a receptor of the closely related nonapeptide vasopressin has also been associated with ASD [40][41][42]. This provisional role of OT in ASD, is further supported by two linkage studies [43,44], clinical evidence by several groups demonstrating clinical improvement in ASD following OT administration [45][46][47][48][49][50][51] (also see [52,53]) and studies showing that ASD is also associated with alterations in OT plasma levels [54].…”
Section: Oxytocin and Autism Spectrum Disorders (Asd)mentioning
confidence: 91%
“…Interestingly, the AVPR1a receptor of the closely related nonapeptide vasopressin has also been associated with ASD [40][41][42]. This provisional role of OT in ASD, is further supported by two linkage studies [43,44], clinical evidence by several groups demonstrating clinical improvement in ASD following OT administration [45][46][47][48][49][50][51] (also see [52,53]) and studies showing that ASD is also associated with alterations in OT plasma levels [54].…”
Section: Oxytocin and Autism Spectrum Disorders (Asd)mentioning
confidence: 91%
“…Human studies have focused on pharmacological administration and the measurement of plasma neuropeptides, mainly of OXT. It has been suggested that intranasal OXT is beneficial for the remission of autistic symptoms by improving cooperation and sense of trust [15] as well as by enhancing social responsiveness [16] and social reciprocity [17].…”
Section: Introductionmentioning
confidence: 99%
“…Four studies have shown lower plasma OXT levels in children with ASD than in control individuals [15,[18][19][20], two studies have reported higher OXT levels [21,22], and one has reported no overall group difference [23]. Relationships between plasma OXT levels and social behaviors were either not investigated [15,21] or were analyzed in subsets or subtypes of ASD [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several studies have shown that administering oxytocin improves symptoms of autism. Intranasal oxytocin improves the ability of young autistics to recognize emotions in the ''Reading the Mind in the Eyes'' task (Guastella et al, 2010) and increases the positive feelings of interacting socially in a simulated ball toss game and increases preference for reciprocal relationships (Andari et al, 2010).…”
Section: Neuroendocrine Hypothesismentioning
confidence: 99%